Natural beauty of modern art philosophy: evaluation of the art form of sport ice and snow sculpture in landscape architecture - Jiahao Chen; Jiaxuan Chen; Liquan Chen (Trans/Form/Ação)
To reveal how sport ice and snow sculptures redefine natural beauty, in the context of modern art, and explore their implications for landscape architecture design, this article uses a combination of literature review and case analysis to explore the aesthetic value, artistic form, and philosophical foundation of sport ice and snow sculptures in gardens and analyzes specific cases of sport ice and snow sculpture art forms in landscape architecture. Research has shown that the understanding of natural beauty, by modern art philosophy, has gone beyond the scope of traditional aesthetics and is more concerned with the interaction between nature and humans. Sport ice and snow sculpture is a unique form of landscape architecture that not only embodies the aesthetic characteristics of natural materials, but also expresses profound reflections on the natural environment through technological innovation, artistic creation and other means. This article provides a new perspective on the creation of landscape architecture and further enriches the aesthetic connotation of modern gardens.